1985
DOI: 10.1136/ard.44.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of rheumatoid factors by an enzyme-linked immunosorbent assay (ELISA) and comparison with other methods.

Abstract: SUMMARY IgM rheumatoid factor (RF) was measured in the sera of 48 rheumatoid patients and of 48 age and sex-matched normal controls by the Rose-Waaler and latex agglutination tests, a rate nephelometer, and an enzyme-linked immunosorbent assay (ELISA). Good correlation was obtained between all assays. The rate nephelometer assay was the easiest and quickest to perform and gave results in international units/ml. The Rose-Waaler was the least sensitive assay and the most difficult to perform and interpret. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Without digestion, the specificity of IgG RF, and as a result of having all 3 isotypes correctly measured, is much lower 19,28,29 . This is likely due to nonspecific interaction between IgG on the solid phase and IgG in the patient's serum 5,6,10 . Thus, the clinician places a completely different emphasis on the RF test results for making the diagnosis if the isotype composition is known, which may be particularly valuable for early diagnosis or when the presentation is ambiguous, an aspect that deserves further support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Without digestion, the specificity of IgG RF, and as a result of having all 3 isotypes correctly measured, is much lower 19,28,29 . This is likely due to nonspecific interaction between IgG on the solid phase and IgG in the patient's serum 5,6,10 . Thus, the clinician places a completely different emphasis on the RF test results for making the diagnosis if the isotype composition is known, which may be particularly valuable for early diagnosis or when the presentation is ambiguous, an aspect that deserves further support.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, appropriate identification of RF+ patients in the screening process is essential. It has been shown that ELISA is significantly more sensitive than turbidimetry in detecting RF IgM 6 . Indeed, at the same level of specificity, 97%, we identified 282 RF+ specimens by ELISA and 218 by turbidimetry (Table 1).…”
Section: Rheumatologymentioning
confidence: 99%
See 1 more Smart Citation
“…Polystyrene plates (Maxisorb; Nunc, Rochester, NY) were coated with purified and heat-aggregated (631C for 20 min) human (IgM RF test) or rabbit IgG (IgA and IgG RF determinations) (40.0 mg/mL) in NaHCO 3 (0.05 mol/L, pH 9.6) according to previous studies (31)(32)(33)(34)(35), and quenched with 3% bovine serum albumin (BSA) fraction V in phosphate buffered saline-Tween 20 0.05% (PBS-T) (Sigma, St. Louis, MO). An appropriate dilution of serum samples was incubated in the antigencoated wells.…”
Section: Rf Immunoassaysmentioning
confidence: 99%
“…This procedure is based on the ELISA technique described in [14]. Briefly, 50 ~1 IgG (50 pg/ml in carbonate buffer at pH 9.6) was coated onto the wells of a 96-well immuno plate in quadruplicate and allowed to bind at 37°C for 1 h. Following 3 washes in PBS containing 0.05% Tween 20,0.5% SDS in PBS was added to each well to destroy any secondary and tertiary conformation (omission of this step, reduced lectin binding to N-acetylglucosamine by 75%, and to galactose by 25%).…”
Section: Modified Elba To Detect Terminal Carbohydrate Residuesmentioning
confidence: 99%